REHABILITATION OF PATIENTS WITH MULTIPLE AND COMBINED FRACTURES OF FACIAL BONES (Лучшие интеллектуальные исследования, 2025)
Annotation. Rehabilitation of patients with multiple and combined trauma of facial bones with shape memory devices and endoprostheses made of porous titanium nickelide allowed us to achieve good cosmetic, anatomical and functional results in 96% of patients. The peculiarities of facial bone architectonics also require differently shaped fixators and endoprostheses depending on the localization and types of fracture. The methods of treatment of fractures and elimination of defects and deformities of facial skull bones developed by us for the first time in the world can serve as the methods of choice.